Предмет: Математика,
автор: TeaMint
-(5,7-2,9х)-(3,8х-3,7)=-4,9х
Ответы
Автор ответа:
0
- (5,7 - 2,9х) - (3,8х - 3,7) = - 4,9х
- 5,7 + 2,9х - 3,8х + 3,7 = - 4,9х
2,9х - 3,8х + 4,9х = 5,7 - 3,7
4х = 2
х = 2 : 4
х = 0,5
- 5,7 + 2,9х - 3,8х + 3,7 = - 4,9х
2,9х - 3,8х + 4,9х = 5,7 - 3,7
4х = 2
х = 2 : 4
х = 0,5
Похожие вопросы
Предмет: Математика,
автор: 78888888hg
Предмет: Обществознание,
автор: FLOSTGAMER
Предмет: Английский язык,
автор: elenaydalsova2013
Предмет: Химия,
автор: Virdginia
Предмет: Биология,
автор: makarenkovalyuda